Assessment of Different Technological Packaging Systems on the Shelf Life of Meat Products - Noori, Mohammad Asif (Journal of Natural Sciences – Kabul University, 2022)
The primary purpose of food packaging is to extend the shelf life of food and protect it from internal and external spoilage, as well as oxidative factors. Packaging fresh and processed meat aims to prevent contamination, delay spoilage, promote enzymatic activity for developing tenderness, and preserve the color and flavor of the product. Current meat packaging practices range from overwrap packaging for short-term chilled storage to vacuum and modified atmosphere packaging (MAP) systems for long-term chilled storage, each with distinct attributes and applications. Recently, advanced packaging materials and technologies, such as active packaging and smart packaging, have been developed. These innovations are of particular importance for extending the shelf life of food.